Design and Synthesis of 2,6-Disubstituted-4 '-Selenoadenosine-5 '-N,N-Dimethyluronamide Derivatives as Human A(3) Adenosine Receptor Antagonists - Choi, Hongseok; Jacobson, Kenneth A.; Yu, Jinha; Jeong, Lak Shin (MDPI, 2021)
A new series of 4 '-selenoadenosine-5 '-N,N-dimethyluronamide derivatives as highly potent and selective human A(3) adenosine receptor (hA(3)AR) antagonists, is described. The highly selective A(3)AR agonists, 4 '-selenoadenosine-5 '-N-methyluronamides were successfully converted into selective antagonists by adding a second N-methyl group to the 5 '-uronamide position. All the synthesized compounds showed medium to high binding affinity at the hA(3)AR. Among the synthesized compounds, 2-H-N-6-3-iodobenzylamine derivative 9f exhibited the highest binding affinity at hA(3)AR. (K-i = 22.7 nM). The 2-H analogues generally showed better binding affinity than the 2-Cl analogues. The cAMP functional assay with 2-Cl-N-6-3-iodobenzylamine derivative 9l demonstrated hA(3)AR antagonist activity. A molecular modelling study suggests an important role of the hydrogen of 5 '-uronamide as an essential hydrogen bonding donor for hA(3)AR activation.